Performance of Saturated Riparian Buffers in Iowa, USA. Issue 2 (1st March 2019) - Jaynes, D. B.; Isenhart, T. M.
Abstract : Nitrate from artificial drainage pipes (tiles) underlying agricultural fields is a major source of reactive N, especially NO3, in surface waters. A novel approach for reducing NO3 loss is to intercept a field tile where it crosses a riparian buffer and divert a fraction of the flow as shallow groundwater within the buffer. This practice is called a saturated riparian buffer (SRB), and although it is promising, little data on the performance of the practice is available. This research investigated the effectiveness of SRBs in removing NO3 at six sites installed across Iowa, resulting in a total of 17 site‐years. Water flow and NO3 in the tile outlets, diverted into the buffers, and NO3 concentration changes within the buffers were monitored throughout the year at each site. Results showed that all the SRBs were effective in removing NO3 from the tile outlet, with the average annual NO3 load removal ranging from 13 to 179 kg N for drainage areas ranging from 3.4 to 40.5 ha. This is NO3 that would have otherwise discharged directly into the adjoining streams. The annual removal effectiveness, which is the total NO3 removed in the SRB divided by the total NO3 draining from the field, ranged from 8 to 84%. This corresponds to an average removal rate of 0.040 g N m −3 d −1 with a range of 0.004 to 0.164 g N m −3 d −1 . Assuming a 40‐yr life expectancy for the structure and a 4% discount rate, we computed a mean equal annual cost for SRBs of US213.83. Given the average annual removal of 73 kg for all site‐years, this cost equates to 2.94 kg −1 N removed, which is very competitive with other field‐edge practices such as denitrification bioreactors and constructed wetlands. Thus, SRBs continue to be a promising practice for NO3 removal in tile‐drained landscapes. Core Ideas: Saturated riparian buffers (SRBs) removed an average of 73 kg N yr −1 of NO3 from tile water. A buffer with established perennial vegetation is important for optimum NO3 removal. The percentage of NO3 removed to NO3 delivered to a SRB ranged from 8 to 84%. The cost of N removal for this practice is similar to other field‐edge practices.